PELATIHAN PEMANFAATAN DIGITAL MARKETING DALAM PENGEMBANGAN PEMASARAN BAGI PELAKU UMKM - Muhamad Stiadi; Didin Herlinudinkhaji; Yunila Dwi Putri Ariyanti; Nindita Erwanti (Bakti Banua : Jurnal Pengabdian Kepada Masyarakat, 2021)
The purpose of carrying out this community service activity with the theme of using digital marketing in the marketing development of SMEs in the village of Sukorejo is to provide knowledge about digital marketing and training in the application of digital marketing. The method used in the implementation of this activity is through lectures and direct practice of implementing digital marketing. The stages of implementing this event include the opening and introduction of digital marketing, exposure to digital marketing, exposure to some of the problems that are often faced by SMEs, exposure to several foreign terms related to digital marketing then continued with practices related to digital marketing.